2008
DOI: 10.1159/000115847
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Lipid Levels in the Elderly Are Not Associated with the Risk of Mild Cognitive Impairment

Abstract: Background: There are conflicting data relating plasma lipids to the risk of Alzheimer‘s disease (AD). We explored the association of plasma lipids to mild cognitive impairment (MCI), a transitional stage between normal cognition and dementia, in a prospective community-based cohort study among randomly sampled Medicare recipients ≧65 years. Baseline data were collected from 1992 to 1994, follow-up data were collected at 18-month intervals. Methods: Multivariate proportional hazards regression was used to rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 36 publications
3
62
1
Order By: Relevance
“…When we explored the association of plasma lipids to cognitive impairment in these groups we found no significant differences in LDL, HDL, VLDL and total cholesterol levels between AD patients and healthy controls. This is consistent with recent reports decribing no association between lipids and the risk of amnesiac or nonamnesiac mild AD (Reitz et al 2008). However, we found a slightly negative correlation between GDS against total cholesterol, also GDS status against VLDL levels in AD group respect to controls.…”
Section: Discussionsupporting
confidence: 93%
“…When we explored the association of plasma lipids to cognitive impairment in these groups we found no significant differences in LDL, HDL, VLDL and total cholesterol levels between AD patients and healthy controls. This is consistent with recent reports decribing no association between lipids and the risk of amnesiac or nonamnesiac mild AD (Reitz et al 2008). However, we found a slightly negative correlation between GDS against total cholesterol, also GDS status against VLDL levels in AD group respect to controls.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies have shown an association of high LDL, HDL and TG with decline in cognitive performance [44][45][46][47]. Still other studies have shown no association of high LDL, HDL and TG with cognitive functions [48][49][50][51]. Opposite associations were also noted for high LDL and HDL [52][53][54].…”
Section: Discussionmentioning
confidence: 96%
“…Of the studies having examined whole samples without gender stratification, a number of prospective studies found no significant associations with T-C, LDL-C, HDL-C, and TG (Reitz et al, 2005;Reitz et al, 2008;Solfrizzi et al, 2004;Teunissen et al, 2003;van den Berg et al, 2007). Solomon et al reported positive associations between midlife (but not late-life) T-C and cognitive decline in episodic memory and fluency (Solomon et al, 2009).…”
Section: Discussionmentioning
confidence: 99%